Dynamics of Public Deliberation Space in the 2024 Regional Elections in Palembang City and Ogan Ilir Regency - Khairunnas Khairunnas; Indra Tamsyah; Adetia Wulindari (Universitas Pancasakti, 2026)
Public deliberation is a key element of deliberative democracy, as it reflects the quality of citizen participation in political decision-making processes. In the context of local elections (Pilkada), public deliberation functions as a discursive arena for the exchange of arguments, rational reasoning, and the articulation of public aspirations toward candidates’ political agendas. This study aims to analyze the public deliberative space in the 2024 local elections in Palembang City and Ogan Ilir Regency, focusing on three main dimensions: the inclusivity of the public sphere, the rationality of public discourse, and the influence of deliberation on political agendas. Using a qualitative approach, data were collected through in-depth interviews with election management bodies, election supervisory institutions, community leaders, and political observers, complemented by document analysis. The data were analyzed using NVivo 15 to identify thematic patterns and relational dynamics among actors within the deliberative space. The findings indicate that public deliberation in the 2024 local elections in Palembang and Ogan Ilir remains in a transitional phase. While efforts to broaden participation and improve the quality of public discourse are evident, deliberative spaces continue to face limitations in inclusivity, insufficiently substantive discourse rationality, and a weak influence of public aspirations on candidates’ political agendas. These findings highlight the need to strengthen deliberative mechanisms to enhance the quality of local democracy.